Phasing statistics for alpha helical membrane protein structures. (17th September 2013) - Parker, Joanne L.; Newstead, Simon
Abstract: In this report we highlight the latest trends in phasing methods used to solve alpha helical membrane protein structures and analyze the use of heavy atom metals for the purpose of experimental phasing. Our results reveal that molecular replacement is emerging as the most successful method for phasing alpha helical membrane proteins, with the notable exception of the transporter family, where experimentally derived phase information still remains the most effective method. To facilitate selection of heavy atoms salts for experimental phasing an analysis of these was undertaken and indicates that organic mercury salts are still the most successful heavy atoms reagents. Interestingly the use of seleno‐l ‐methionine incorporated protein has increased since earlier studies into membrane protein phasing, so too the use of SAD and MAD as techniques for phase determination. Taken together this study provides a brief snapshot of phasing methods for alpha helical membrane proteins and suggests possible routes for heavy atom selection and phasing methods based on currently available data.